Automated palm oil supply chain system with traceability - Rahman, Md. Arafatur; Sze Wei, Tan; Rahman, Md Mustafizur; Md Muzahid, Abu Jafar (2021)
Palm oil tree is very suitable to grow in Malaysia since Malaysia’s climate is equatorial ; hot, humid and also rainy throughout the year. Palm oil production is vital for the economy of Malaysia. However, Palm Oil Industry in Malaysia is still using the traditional Supply Chain Management. This product able to increase the efficiency and reliability of palm oil supply chain system. Allow consumer to review the information of palm oil manufacturing process from harvesting to packaging.